PELAYANAN PUBLIK PADA MASA PANDEMI COVID-19 DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - Fhebri Wulandira Biu Mairi; Stefanus ., Sampe; Leviane Jacklin Hera Lotulung (Sam Ratulangi University, 2021)
This study aims to determine public services during the Covid-19 pandemic in Bahu Sub-District, Malalayang District, Manado City, and also to find out how the Bahu Sub-District government strategy in providing services to the community during the Covid-19 pandemic. The research method used is qualitative research methods. The data is poured descriptively and collected through observation, documentation and in-depth interviews with the Head of the Sub-District, the Secretary of the Sub-District, the Head of the Public Service Section and several communities. The results showed that public services during the Covid-19 pandemic in the Bahu Sub-District, Manado City were still provided directly to the community by implementing a service shift system for village employees. Services to the community have been carried out based on components of public service standards but have not been maximal in service mechanisms, handling complaints and suggestions and implementing health protocols. The Bahu Sub-District government in serving the community must further maximize services in terms of service mechanisms and implementing health protocols through socialization and education to the public as a step to avoid the spread of Covid-19 and make health protocols a new normal habit. In addition, it utilizes communication information technology to provide information to the public and pay more attention to the media that has been provided to respond to complaints, suggestions and input from the public regarding the services provided.